Diaries as Technologies for Sense-making and Self-transformation in Times of Vulnerability - Bernal Marcos, Marcos José; Zittoun, Tania; Alex Gillespie (My University, 2023)
Diaries have been generally understood as “windows” on sense-making processes when studying life ruptures. In this article, we draw on Michel Foucault’s conceptualization of self-writing as a “technology of the self” and on sociocultural psychology to propose that diaries are not “windows” but technologies that aid in the sense-making. Concretely, we analyzed three non-exhaustive and non-exclusive uses of diary writing in times of vulnerability: (1) imagination of the future and preparation to encounter difficulties; (2) distancing from one’s own experience; and (3) creating personal commitments. Our longitudinal data comprised three public online diaries written over more than twenty years, belonging to three anonymous individuals selected from a database of more than 400 diaries. We analyzed these three diaries by iterating between qualitative and quantitative analysis. We conclude that: (1) beyond their expressive dimension, diaries are technologies that support the sense-making process, but not without difficulties; (2) diaries form a self-generated space for dialogue with oneself in which the diarist also becomes aware of the social nature of her life story; (3) diaries are not only technologies for the Socratic “know thyself” but also technologies to work on oneself, especially in terms of the personal perspective on the past or the future; and (4) the practice of diary writing goes beyond sense-making towards personal development and the desire to transform one’s life trajectory.
Keywords: Diaries · Sense-making · Technologies of the self · Vulnerability · Life course